Assessing the stability of protective structures in preparatory mining workings under conditions of static load - Chepiga, Daria; Podkopaiev, Serhii; Kayun, Oleksiy; Bielikov, Anatolii; Podkopayev, Yevgen; Kipko, Oleksandr; Pidhurna, Olha (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the deformation processes in protective structures under the action of static load in the coal massif in order to preserve the integrity of the side rocks and the operational condition of mine workings. Under laboratory conditions, the deformation characteristics of rigid and flexible protective structures, as well as supports made of crushed rock, were studied on experimental samples. The samples were subjected to uniaxial compression. It was established that there is a functional relationship between the coefficient of transverse deformation ν and the relative change in the volume δV of protection structures, which makes it possible to estimate their bearing capacity. For rigid protection structures (coal pillars, cast strip, cement blocks, blocks of reinforced concrete bollards, bundles of wooden racks), the deformed state of the structures determines their behavior. This happens at values of ν=0.3–0.5 and δV£0.09. Their stability is fixed within the safe deformation resource. An increase in the deformation energy density of such structures beyond the safe deformation resource leads to their destruction due to a change in shape. For flexible protection structures (bundles of wooden racks, rolling bundles made of wooden sleepers), which have a transverse deformation coefficient ν=0.02, at a relative change in volume δV£0.3, the compaction of structures is observed. Increasing their stiffness allows limiting the convergence of side rocks. For a support made of crushed rock, at ν=0.25–0.32 and a relative volume change of 0.12£δV£0.32, its compaction and increase in resistance occur. Under such conditions, the convergence of side rocks is limited. In order to preserve the integrity of the lateral and operational condition of preparatory workings in the excavation areas of coal mines, it is advisable to use flexible protective structures made of wood or supports made of crushed rock